Step-by-step explanation:
v(-2)= 12-2x(-2)-5
=12+4-5
=16-5
=11
v(0)= 12-2x0-5
= 12-0-5
=12-5
=7
v(5)= 12-2x5-5
= 12-10-5
=12-5
=7
<em><u>Hope </u></em><em><u>it </u></em><em><u>helps </u></em>
Let
In order to prove this by induction, we first need to prove the base case, i.e. prove that P(1) is true:
So, the base case is ok. Now, we need to assume and prove .
states that
Since we're assuming , we can substitute the sum of the first n terms with their expression:
Which terminates the proof, since we showed that
as required
Answer:
The answer is 13 1/6
Step-by-step explanation:
The answer is 18 because 7 1/3 turns into 7 2/6 and 7 * 6 is 42 and 42 plus 2 is 44. Next You turn 5 5/6 into a improper fraction which turns into 35/6 and 35 plus 44 is 79/6 and 79/6 simplified is 13 1/6